Why nations fail : the origins of power, prosperity and poverty - Acemoglu, Daron; Robinson, James A., 1960-. (New York : Crown Publishers, 2013)
Why are some nations rich and others poor? Is it culture, the weather, geography? Perhaps ignorance of the right policies? Simply, no. None of these factors is either definitive or destiny. Daron Acemoglu and James Robinson conclusively show that it is ma
Preface: Why Egyptians filled Tahrir Square to bring down Hosni Mubarak and what it means for our understanding of the causes of prosperity and poverty -- So close and yet so different : Nogale.
Includes bibliographical references (p. [465]-509) and index.
Keywords: Economics -- Political aspects; Economic history -- Political aspects; Poverty -- Developing countries; Economic development -- Developing countries; Revolutions -- Economic aspects; Developing countries -- Economic policy; Developing countries -- Social policy; Yoksulluk -- Gelişmekte olan ülkeler; Gelişmekte olan ülkeler -- Ekonomik politika; Ekonomik kalkınma -- Az gelişmiş ülkeler; Ekonomik kalkınma -- Gelişmekte olan ülkeler; Ekonomi -- Politik yönü; Ekonomi -- Siyasal yönler; Devrimler -- Ekonomik yönü